Miscibility, crystallization and properties of bio-based polyamide 56/polyamide 6 blends. (16th January 2023) - Wang, Zhe; Lin, Na; Kang, Hongliang; Hao, Xinmin; Liu, Ruigang
Abstract: The miscibility, crystallization behaviors, and morphology of polyamide 56/polyamide 6 (PA56/PA6) blends were investigated. The blends had only one T g, which confirmed that PA56 and PA6 are miscible in the blends. The melting point, crystallization temperature, crystallinity of the blends depressed due to the interaction of PA56 and PA6 in the blends. The crystalline structure of both PA56 and PA6 in the blends did not change and crystallized separately in both isothermal and non-isothermal crystallization process. PA56 in the blends crystallized in all blending ratio, while PA6 only crystallized with PA6 content φ 6  > 0.2. The crystals of PA56 and PA6 grew in the same crystal skeleton but in different layers. Mechanical properties of the blends indicated that the elongation at break could be improved significantly without scarifying the strength in the case of adding a small amount of PA6 in PA56, which provides a promising approach for fabricating polyamide materials with desired properties. Graphical abstract: Image 1 Highlights: PA56 and PA6 are miscible in PA56/PA6 blends. PA56 and PA6 crystallize separately in the blends without change in their crystalline structure. PA56 and PA6 crystals grow in the same crystalline skeleton but in different layers. The elongation at break of PA56/PA6 blends is enhanced tremendously at low PA6 content.